7A.03: TRANSGENERATIONAL INHERITANCE OF GENOME-WIDE DNA METHYLATION PROFILES IN PULMONARY VASCULAR ENDOTHELIAL DYSFUNCTION FOLLOWING EXTRAUTERINE GROWTH RESTRICTION. (June 2015) - Zhang, L.; Du, L.; Tang, L.; Lao, L.; Hu, Q.
Abstract : Objective: Early postnatal life is considered as a critical time window for determination of long-term metabolic states and organ functions. Extrauterine growth restriction (EUGR) causes the development of adult onset chronic diseases, including pulmonary hypertension (PH). However, the mechanisms involved and the possibilities of transgenerational transmission on pulmonary vascular consequences in later life are still unclear. Epigenetic information can be inherited and represents a plausible transgenerational carrier of environmental information. Our study was designed to test whether epigenetics dysregulation mediates the cellular memory of this early postnatal event. Figure. No caption available. Design and method: To test this hypothesis, the EUGR pups were established by undernutritional until weaning. We isolated pulmonary vascular endothelial cells (PVEC) by magnetic-activated cell sorting (MACS) from EUGR and control rats. MeDIP-chip (Methyl-DNA immune precipitation chip), genome-scale mapping studies to search for differentially methylated loci. A postnatal insult, nutritional restriction-induced EUGR caused development of an increased PH at 9-week of age in male rats (First-generation of EUGR, F1-EUGR male). We intercrossed female adult control and F1-EUGR-male rats to obtain the second-generation (F2) offspring in two groups: C male-C female, EUGR-male -C-female. Results: We found that significantly decreased pulmonary artery pressure in F2 female offspring in EUGR-male-C-female group (F2-EUGR-female), compared with controls to some degrees. we carried out genome-wide DNA methylation profiles screen for genes in rats between F1-EUGR-male and F2-EUGR-female. The EUGR and control group comparisons revealed consistently and distinctively methylated loci, with 74.8% F1-EUGR-male group and 84.5% F2-EUGR-female group changes in hyper-methylation loci enriched for highly significant group differences. Gene ontology (GO) analysis on no consistent differentially methylated genes (approximately 37%) between F1-EUGR-male and F2-EUGR-female groups showed that are lipid metabolic process, calcium signaling, methylation and PH-associated genes. We validated candidate dysregulated loci with quantitative assays of cytosine methylation and gene expressions. Conclusions: These results, in conjunction with recent human epidemiological data, demonstrate that DNA methylation is a strong mechanism for propagating the cellular memory of early postnatal events, causing changes in expression of genes and transgenerational transmission on pulmonary vascular consequences in later life.